Relation between Interleukin-6, Interleukin-10 and Interleukin-2 Receptor and mortality in Severely Ill COVID-19 patients - Asmaa Embarak Hassan; Nahla Abdelaziz Nosair; Mohammed Hussien Ahmed; Dalia Elsayed Sherif; Eman Mohammad Habib; Nahla Farahat (Journal of the Pakistan Medical Association, 2023)
Objective: To investigate the relation involving soluble interleukin-2 receptor, interleukin-6 and interleukin-10 in hospitalised patients with severe coronavirus disease-2019 infection. Methods: This single-centre cohort study was conducted at the Kafrelshiekh University Hospital, Egypt, from January to June 2022, and included all patients of either gender who were hospitalised with severe infection with the coronavirus disease-2019 isolation ward. Chemiluminescence immunoassay method was used to measure levels of procalcitonin, ferritin, soluble interleukin-2 receptor, interleukin-6 and interleukin-10. Data was analysed using SPSS version. 25 Results: Of the 250 patients with median age 57.5 years (interquartile range: 45.8-66.0 years), 147(59%) were males and 103(41%) were females. Of them, 102(40.8%) patients died; 68(66.7%) males, 34(33.3%) females, median age 60.0 years (interquartile range: 48.8-70.0). Among the 148(59.2%) survivors, 79(53.4%) were males and 69(46.6%) were females, while the overall median age was 55.0 years (interquartile range: 41.5-65.8 years). The survivors had significantly lower levels of soluble interleukin-2 receptor, interleukin-6 and interleukin-10 (p<0.001). Correlation analysis identified significant positive correlation between IL-2R, IL-6 and IL-10 levels and almost all the inflammatory and coagulation parameters, including C-reactive protein, lactate dehydrogenase, procalcitonin, ferritin, D-dimer and fibrinogen (p<0.05). Conclusion: Elevated levels of soluble interleukin-2 receptor, interleukin-6 and interleukin-10 were found to be associated with greater risk of mortality in coronavirus disease-2019 patients. Keywords: Interleukin-6, Interleukin-10, Procalcitonin, Fibrin fragment D, COVID-19, Luminescence, Interleukin-2, Immunoassay, Fibrinogen, Ferritins